How French subjects describe well-being from food and eating habits? Development, item reduction and scoring definition of the Well-Being related to Food Questionnaire (Well-BFQ©). (1st January 2016) - Guillemin, I.; Marrel, A.; Arnould, B.; Capuron, L.; Dupuy, A.; Ginon, E.; Layé, S.; Lecerf, J.-M.; Prost, M.; Rogeaux, M.; Urdapilleta, I.; Allaert, F.-A.
Abstract: Providing well-being and maintaining good health are main objectives subjects seek from diet. This manuscript describes the development and preliminary validation of an instrument assessing well-being associated with food and eating habits in a general healthy population. Qualitative data from 12 groups of discussion (102 subjects) conducted with healthy subjects were used to develop the core of the Well-being related to Food Questionnaire (Well-BFQ). Twelve other groups of discussion with subjects with joint (n = 34), digestive (n = 32) or repetitive infection complaints (n = 30) were performed to develop items specific to these complaints. Five main themes emerged from the discussions and formed the modular backbone of the questionnaire: "Grocery shopping", "Cooking", "Dining places", "Commensality", "Eating and drinking". Each module has a common structure: items about subject's food behavior and items about immediate and short-term benefits. An additional theme – "Eating habits and health" – assesses subjects' beliefs about expected benefits of food and eating habits on health, disease prevention and protection, and quality of ageing. A preliminary validation was conducted with 444 subjects with balanced diet; non-balanced diet; and standard diet. The structure of the questionnaire was further determined using principal component analyses exploratory factor analyses, with confirmation of the sub-sections food behaviors, immediate benefits (pleasure, security, relaxation), direct short-term benefits (digestion and satiety, energy and psychology), and deferred long-term benefits (eating habits and health). Thirty-three subscales and 14 single items were further defined. Confirmatory analyses confirmed the structure, with overall moderate to excellent convergent and divergent validity and internal consistency reliability. The Well-BFQ is a unique, modular tool that comprehensively assesses the full picture of well-being related to food and eating habits in the general population. Highlights: A qualitative phase in healthy subjects was conducted to develop the Well-BFQ. The Well-BFQ considers social and environmental aspects related to food. The Well-BFQ measures immediate, short-term and long term food-related well-being. The Well-BFQ scoring is available. The Well-BFQ has a unique modular structure allowing specific aims to be addressed.